Event-triggered ε level H∞ probabilistic control of uncertain systems - Yin, YanYan; Liu, Y.; Teo, Kok Lay; Wang, Song; Liu, F. (Elsevier, 2018)
The Franklin Institute In this paper, a new event-trigger based probabilistic controller is designed using a scenario optimization approach for the robust stabilization of uncertain systems subject to nonlinear and unbounded uncertainties. Sufficient probabilistic stabilization conditions are derived under which the closed-loop system is e level robust probabilistic stable. Based on these conditions, the design of the gains of the event-triggered state feedback controller is formulated and solved as an optimization problem involving linear matrix inequality. The applicability of theoretical results obtained is illustrated by a numerical example.